Ependymoma‐like tumor with mesenchymal differentiation harboring C11orf95‐NCOA1/2 or ‐RELA fusion: A hitherto unclassified tumor related to ependymoma. (12th February 2021) - Tomomasa, Ran; Arai, Yasuhito; Kawabata‐Iwakawa, Reika; Fukuoka, Kohei; Nakano, Yoshiko; Hama, Natsuko; Nakata, Satoshi; Suzuki, Nozomi; Ishi, Yukitomo; Tanaka, Shinya; Takahashi, Jun A.; Yuba, Yoshiaki; et al.
Abstract: Recurrent fusion genes involving C11orf95, C11orf95 ‐ RELA, have been identified only in supratentorial ependymomas among primary CNS tumors. Here, we report hitherto histopathologically unclassifiable high‐grade tumors, under the tentative label of "ependymoma‐like tumors with mesenchymal differentiation (ELTMDs), " harboring C11orf95 ‐ NCOA1 / 2 or ‐ RELA fusion. We examined the clinicopathological and molecular features in five cases of ELTMDs. Except for one adult case (50 years old), all cases were in children ranging from 1 to 2.5 years old. All patients presented with a mass lesion in the cerebral hemisphere. Histologically, all cases demonstrated a similar histology with a mixture of components. The major components were embryonal‐appearing components forming well‐delineated tumor cell nests composed of small uniform cells with high proliferative activity, and spindle‐cell mesenchymal components with a low‐ to high‐grade sarcoma‐like appearance. The embryonal‐appearing components exhibited minimal ependymal differentiation including a characteristic EMA positivity and tubular structures, but histologically did not fit with ependymoma because they lacked perivascular pseudorosettes, a histological hallmark of ependymoma, formed well‐delineated nests, and had diffuse and strong staining for CAM5.2. Molecular analysis identified C11orf95 ‐ NCOA1, ‐ NCOA2, and ‐ RELA in two, one, and two cases, respectively. t‐distributed stochastic neighbor embedding analysis of DNA methylation data from two cases with C11orf95 ‐ NCOA1 or ‐ NCOA2 and a reference set of 380 CNS tumors revealed that these two cases were clustered together and were distinct from all subgroups of ependymomas. In conclusion, although ELTMDs exhibited morphological and genetic associations with supratentorial ependymoma with C11orf95 ‐ RELA, they cannot be regarded as ependymoma. Further analyses of more cases are needed to clarify their differences and similarities. Abstract : We report hitherto histopathologically unclassifiable high‐grade tumors, ELTMDs. ELTMDs exhibited minimal ependymal differentiation and C11orf95‐NCOA1/2 or ‐RELA.